2003
DOI: 10.1590/s0100-879x2003000900003
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and p53 protein expression in vulvar intraepithelial neoplasia and invasive squamous cell carcinoma

Abstract: The etiopathogenesis of vulvar intraepithelial neoplasia (VIN III) and invasive squamous cell carcinoma are largely unknown. Since there are few studies on Brazilian patients, our purpose was to determine the frequency of human papillomavirus (HPV) infection and the expression of p53 in these lesions, and associate them with other factors such as age, morphological subtypes, multicentric and multifocal disease. Thirty-eight cases of VIN III, nine of superficially invasive carcinoma, and 55 of invasive vulvar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…7,12,[14][15][16][17][19][20][21][22]27,31 In this report, low-risk HPV types in general were infrequently encountered, and only three invasive squamous vulvar carcinoma cases were identified that contained only low-risk HPV genotypes, correlating with previous work. 7,19,21,22,27,31 Interestingly, one case where lowrisk HPV26 was identified in a primary warty carcinoma also demonstrated HPV26 in a lymph node which contained metastatic squamous carcinoma.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…7,12,[14][15][16][17][19][20][21][22]27,31 In this report, low-risk HPV types in general were infrequently encountered, and only three invasive squamous vulvar carcinoma cases were identified that contained only low-risk HPV genotypes, correlating with previous work. 7,19,21,22,27,31 Interestingly, one case where lowrisk HPV26 was identified in a primary warty carcinoma also demonstrated HPV26 in a lymph node which contained metastatic squamous carcinoma.…”
supporting
confidence: 81%
“…Multiple authors have suggested that vulvar cancer comprises two separate diseases, the first type occurring with high prevalence among young women and developing from vulvar intraepithelial neoplasia caused by HPV, and a second type afflicting older women and developing from non-neoplastic epithelial disorders such as lichen sclerosus or chronic inflammation. [2][3][4]12,13,15,18,24,25 However, these studies of HPV prevalence in invasive squamous vulvar carcinoma also utilized different methods of detection, including in-situ, [13][14][15][16][17][18] dot blot, 20,21 and Southern blot 20 hybridization, immunohistochemistry, 15 and PCR-based assays, 2,7,12,18,19,[22][23][24][26][27][28][29][30][31][33][34][35][36] each with different analytic sensitivities. Moreover, the particular HPV genotype(s) targeted in previous work is inconsistent between studies; many early reports documented only HPV16, 18, 33, and/or 6/11, 18,20,21,26,[28][29]…”
mentioning
confidence: 99%
“…In classic vulvar intraepithelial neoplasia, a HPV positivity of 66.1% was reported confirming the high presence of HPVs in this histological type of lesions. The prevalence of HPV positivity in vulvar intraepithelial neoplasias and vulvar squamous cell carcinoma (from 31% up to 90%), reported in the literature [Park et al, 1991;Hording et al, 1995;Sun et al, 1996;Trimble et al, 1996;Hildesheim et al, 1997;Iwasawa et al, 1997;Kagie et al, 1997;Gastrell and McConnell, 2001;Hart, 2001;McNally et al, 2002;Engelman et al, 2003] has a broad range and the values differ greatly from one study to another: HPV has been searched for in various geographical regions, in subjects with different immunological status, sometimes unregarding the histological type of vulvar lesions, studying classic and differentiated vulvar intraepithelial neoplasias and vulvar squamous cell carcinoma together, and using methodologies (serology, histology, in situ hybridization, PCR) with different sensitivities and sometimes directed to detect only the presence of HPV 16. In the present study, the predominant HPV type found in classic vulvar intraepithelial neoplasia was HPV 16 (81.8%), with 35, 33, and 52 types rarely found and sometimes in concomitance with the presence of 16 HPV type; this finding is in accordance with the majority of reports [Hording et al, 1995;Trimble et al, 1996;Gastrell and McConnell, 2001;Hart, 2001;Engelman et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tumors harboring p53 mutations often accumulate nonfunctional p53 protein in the cell, which is detectable by immunohistochemistry. Although not allowing for the exact identification of the underlying carcinogenic events, p16 INK4a and p53 immunohistochemistry has been acknowledged as a valuable tool to discriminate between different types of vulvar cancer [7,13].…”
mentioning
confidence: 99%